The Facilities-Related Issues in Public University Buildings: A Case Study at Universiti Tun Hussein Onn Malaysia (UTHM) - Ng, Jia Yy; Yasin, Mohd Norazam (Recent Trends in Civil Engineering and Built Environment, 2025)
Public universities, exemplified by Universiti Tun Hussein Onn Malaysia (UTHM), must prioritize the upkeep of well-maintained and modern facilities, encompassing classrooms, laboratories, and libraries, to cultivate an optimal learning environment fostering both student success and a sense of community. The objectives included identifying these issues, understanding their consequences on users, and proposing preventive measures to address them. Neglecting challenges such as insufficient space, outdated equipment, and accessibility issues can detrimentally affect the quality of education and research, impacting students and staff alike. The study at UTHM employed a quantitative approach, utilizing a structured questionnaire with 240 respondents, analyzed through Statistical Package for Social Science (SPSS) version 27. The findings, ranked by the Relative Importance Index (RII), underscored safety, health, and well-being as the top consequences of facilities-related issues, with an RII value of 0.91. Following closely was the potential decrease in the university’s reputation and image, registering an RII value of 0.90, while impacts on comfort and extracurricular activities ranked lower with an RII value of 0.83. Lastly, the research emphasizes the pivotal role of a robust maintenance department in proactively managing and enhancing problem-solving capabilities to address building-related issues, safeguarding the overall condition, safety, and functionality of university facilities. Neglecting these issues not only jeopardizes safety and well-being but also entails significant financial implications, underscoring the importance of comprehensive preventive measures in the context of public university infrastructure like UTHM.